The 2018 peoples' global conference against the International Monetary Fund and World Bank in Bali, Indonesia - Enrile, Ivan Phell ([Quezon City] Asia Pacific Research Network, 2019)
This book is a compilation of the analyses and insights of peoples' movements and their communities that are directly affected by the deleterious impacts of the IMF-World Bank's policies and projects. It is also a documentation of the courage of peoples' movements defending their rights and sovereignty in the face of heavy repression
Resist IMF-World Bank, imperialist istrument for exploiting the world's people. -- The people's global conference. -- Communique of the people's global conference agaisnt IMF and World Bank. -- Shut down the IMF-World Bank, not the people's dissent!: fight for people's right to development. -- Jose Maria Sison. -- Len Cooper. -- Rafael Mariano. -- Amy Padilla. -- Workshop proceedings. -- Statements. -- Ivan Enrile. -- Organizations Keynote address On the corporatization of development IMF-WBG and landgrabbing: funding rural peoples' destitution World Bank "solutions" still sugarcoat failed economic assumptions Negotiating spaces for engagement and resistance
Keywords: Anti-imperialist movements -- Congresses; Imperialism -- 21st century -- Congresses; International Monetary Fund; World Bank